Peranan Strategi Pemasaran Dalam Upaya Peningkatan Penjualan Produk UMKM Yogyakarta - Willy Adimas Rahmawan; Lukman Dwi Rismanto; Muinah Fadhilah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This research was conducted to find out the marketing strategy implemented by UMKM Yogyakarta by utilizing technology in the era of society 5.0. This study uses the BCG analysis method whose data comes from MSME financial statements. The results obtained show that marketing through social media is the right technique for UMKM Yogyakarta.